Development of a More Accurate Dynamic Bias Error Model for Two-Phase Flow Measurements Performed with Radiation Transmission - Diaz, Julio; Serrano-Aguilera, Juan José; Petrov, Victor; Manera, Annalisa (Elsevier, 2021)
Application of radiation transmission measurement of two-phase flow phenomena has surged in the past decades due to the advancements in radiation detection along with its non-intrusive nature in comparison with other advanced two-phase flow measurements instrumentation such as wire mesh sensors and needle probes. However, radiation transmission measurement entails various levels of complexity when measuring temporally varying signals, which is the case for two-phase flow phenomena. The time-integrated radiation transmission acquisition yields a biased result, known as dynamic bias. In the present study, a more accurate method to estimate the dynamic bias is formulated. In addition, the behavior of the dynamic bias in two-phase flow measurements is investigated and characterized as a function of the void-fraction's temporal phase distribution, the gas phase magnitude distribution, and the contrast attenuation between the liquid and gas phases. Both numerical simulations and actual measurements of two-phase flows obtained with wire-mesh sensors, which includes several flow patterns, are used in the study. The dynamic bias was simulated for a contrast attenuation factor, λ, ranging from 0.01 to 5; this is a dimensionless factor that considers the geometry, elemental composition of the phases, radiation type and energy. The RMSE error was estimated for the proposed model and the reference model derived by Harms; the RMSE percentage decrease for the proposed model relative to Harm's for the range of λ improves by 50% to 58% for the bubbly regime, 40% to 59% for the bubbly to churn transitional regime, 36% to 56% for the churn regime, and 15% to 56% for the wispy annular.
Keywords: Flujo bifásico; Radiation Transmission; Void Fraction; Dynamic Bias; Two-Phase Flow